Effect of Pattern Coating Thickness on Surface Roughness and Porosity of Nodular Cast Iron (FCD) 450 Using Lost Foam Casting Method - Kardo Rajagukguk; Suyito (Cylinder : Jurnal Ilmiah Teknik Mesin, 2018)
Lost foam casting is one of casting method that uses expanded polystyrene (EPS) foam as a mold pattern and embedded into silica sand. When the molten metal is poured into a mold, EPS will melt and evaporate, so the cavity is filled by the molten metal. The main objective of this research was to investigate the effect of pattern coating thickness on surface roughness and porosity of nodular cast iron FCD 450 by using the lost foam casting method. The mold pattern of EPS foam has 17 kg/m3 of density and 3-24 mm of section thickness. Coating material was used a refractory material of Zircon (ZrO2) and binder of Colloidal Silica (O2Si). In order to study effects of coating thickness, experiments were conducted with of 0-1300 μm. FCD 450 metal alloy was melted in a crucible furnace and the molten metal was poured into a mold at temperatures of 1350 °C-1450 °C. The experimental results showed the surface roughness decreases with increasing coating thickness of the EPS pattern. Uncoated of EPS pattern influenced the casting quality. The porosity increases with coating thickness of EPS pattern.